PELA for a smaller, not-for-profit campus: Our story - Dench, Alison (Journal of Academic Language and Learning, 2024)
This article outlines the step-by-step process one small tertiary education provider is taking in establishing a Post-entry Language Assessment (PELA) on campus. Sheridan Institute of Higher Education has less than 100 students, is not-for-profit, upholds face-to-face learning, and has only one faculty member functioning as Academic Language and Learning (ALL) staff. In these ways, it is unique. Challenges have ensued around transitioning into a new system, dealing with student perceptions of what the PELA entails, completing the whole process within a reasonable time frame, and needing a high level of faculty participation. One highlight is the development of three compulsory undergraduate research units that underpin Sheridan’s embedding of academic literacies. Suggestions for further development and research have been included.